KETUPAT EID TRADITION OF THE NORTH COAST OF JAVA AS AN ALTERNATIVE MATHEMATICS LEARNING MEDIA - Wikan Budi Utami; Fikri Aulia; Dian Permatasari; Muhammad Taqiyuddin; Sri Adi Widodo (IKIP Siliwangi and I-MES, 2022)
Learning mathematics requires real situations that students often face. Tradition as local wisdom from the surrounding community can be used for learning mathematics so that students can reach the context of abstract mathematics. In this article, the researcher explains how teachers can take advantage of local culture and traditions in the form of Ketupat Eid on the north coast of Java to be used in learning mathematics. This research was conducted on the northern coast of Java, where every seventh day after Eid Mubarak, the area performs the Ketupat Eid tradition. Researchers tried to connect some foods that only exist in the Ketupat Eid tradition in the form of Ketupat and Lepet with mathematics in school. The results showed that diamonds could be used for rhombuses, prisms, and beams, and Lepet can be used as a tube context in geometry learning.